Indonesia’s export growth decomposition in ASEAN and ASEAN dialogue partners - Setyoko, Nur Rakhman; Rokhim, Rofikoh; Rohman, Ibrahim Kholilul; Rofii, Muhammad Syaroni (Universitas Islam Indonesia, 2024)
Purpose ― This paper evaluates Indonesia's trade integration efforts and their impact on export competitiveness from 1989 to 2021. It examines the evolution of trade arrangements, starting with the ASEAN Preferential Trade Arrangement (APTA) and progressing to bilateral agreements.Methods ― Based on Leamer and Stern, the Constant Market Share Analysis (CMSA) measures Indonesia’s export competitiveness over the years.Findings ― The results indicate no significant improvement in competitiveness during the analysis period, with export growth primarily driven by the effect of world growth. Although competitiveness did not shift markedly over time, it remained positive overall, suggesting a buffer effect during economic crises.Implications ― The paper suggests Indonesia should pursue deeper trade integration and unilateral economic reforms. Drawing on Korea’s experience, combining export promotion policies with trade agreements could enhance market access and foster internal competitiveness.Originality ― This study provides long-term insights into Indonesia’s export competitiveness amidst global trade integration efforts and offers policy recommendations based on the success of Korea’s trade reforms.